Parameters Identification of Blade Multi-mode Coupled Vibration Based on Blade Tip Timing. Issue 1 (1st January 2023) - Zhi, Fengyao; Duan, Fajie; Li, Jie; Niu, Guangyue; Zhou, Qi
Abstract: Health monitoring is crucial for the safe operation of rotating machinery. As an effective technique for measuring the vibration of rotating blades, blade tip timing (BTT) is widely used since its advantages of non-contact and low intervention. During the operation of high-speed blades, the multi-mode coupled synchronous vibration will occur. However, the existing BTT-based methods cannot identify the multi-mode coupled vibration parameters. To solve the problem, a multi-mode coupled vibration model of the blade based on a slender cantilever beam is established, and the contribution of each mode to the blade vibration response is considered. A new Circumferential Fourier Fit (CFF) method for parameters identification of blade multi-mode coupled synchronous vibration is proposed. According to the proposed method, the reconstruction of multi-mode coupled synchronous vibration signals can be realized. Finally, the accuracy of the proposed method is verified by simulation data.